Factors influencing sustainable community based tourism (CBT) among the indigenous people of Lambir, Sarawak - Lamat, Ripin; Johari, Shazali; Kunasekaran, Puvaneswaran (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The purpose of this paper is to understand the role of community as an important player for community-based tourism in rural areas. Although government’s initiatives are evident, the sustainability of the development is questionable. In this paper, attributes from previous research of local communities’ attitude were reviewed and linked to construct a model within the scope of community tourism. This study is deductive in nature where descriptive statistics used to measure the relevant dimensions. As a result, two themes were measured to have significant contribution in determining local community’s perception on community tourism. This finding can be used in determining sustainable tourism practice which will be focused on participation and empowerment aspects.